Unusual hydrogen explosions due to unanticipated metal‐water reactions. Issue 1 (19th June 2021) - Zalosh, Robert
Abstract: Inadvertent generation of hydrogen from ambient temperature metal‐water chemical and electrochemical reactions have been responsible for a surprising number of hydrogen explosions. This paper describes three sets of incidents involving different metals in applications that are normally considered free of explosion hazards. The first set of incidents involves wet alkaline incinerator ash with an aluminum content of at least 2%. The second set of incidents involves copper conductor electrochemical reactions in subsea electrical cable. The third set involves electrochemical corrosion reactions in galvanized dry sprinkler pipe. In all three applications, test data are discussed to elucidate the specific reactions and potential preventive and mitigation measures.